Problem of interpolation of functions by two-dimensional continued fractions - Pahirya, M. M.; Svyda, T. S. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate the problem of interpolation of functions of two real variables by two-dimensional continued fractions.